Antioxidant and antimicrobial potential of selected varieties of Piper betle L. (Betel leaf) - SARMA,CHAYANIKA (2018)
Abstract Piper betle L., is an evergreen perennial creeper belonging to family Piperaceae and is known to possess numerous medicinal properties. Current study focuses on evaluating antioxidant and antimicrobial potential of betel leaf. For the present study, distilled water, hexane, acetone and ethanolic extracts of two varieties of betel leaves: Meetha paan and Banarasi paan were used. Biochemical tests such as proximate analysis (moisture, ash, protein, lipids, minerals viz., sodium and potassium), antioxidant activity tests (DPPH radical scavenging activity, total phenolics, ascorbic acid, reducing power) and antimicrobial test (antibacterial and antifungal susceptibility test) against four pathogens viz., B. subtilis, E. coli, A. niger and S. cerevisiae were determined. Ethanolic extract had the highest antioxidant activity (89.46% inhibition), while the aqueous extract exhibited lowest antioxidant activity (62.03% inhibition). With increasing concentration (5, 10, 25 and 50 µg/mL), the reducing power of leaf extracts also increased. The ascorbic acid was not significant in Banarasi paan (5.21mg/100 g) and Meetha paan (5.20mg/100 g). The highest antibacterial activity of ethanolic extract (Banarasi paan) may be attributed to the presence of phytosterols in the leaf varieties. Antioxidant and antimicrobial potential study will help to build a database and promote the utilization of betel leaf as a medicinal herb.